2021
DOI: 10.1002/lt.26025
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Risk Stratification in Liver Transplantation: Results of a Tiered Assessment Protocol Based on Traditional Cardiovascular Risk Factors

Abstract: Coronary artery disease (CAD) confers increased perioperative risk in patients undergoing liver transplantation (LT).Although routine screening for CAD is recommended, there are limited data on the effectiveness of screening strategies. We evaluated the safety and efficacy of a 3-tiered cardiac risk-assessment protocol that stratifies patients based on age and traditional cardiac risk factors. We peformed a single-center, prospective, observational study of consecutive adult patients undergoing LT assessment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…In particular, a patient with a long history of PBC and drug-resistant dyslipidemia would be a suitable candidate. According to a recent report, the selective use of dobutamine stress echocardiography, CCTA and coronary angiography would be a safe and feasible approach in LT recipients [ 27 ]. However, considering the medical cost and burden, widespread evaluation in low-risk patients is not realistic.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a patient with a long history of PBC and drug-resistant dyslipidemia would be a suitable candidate. According to a recent report, the selective use of dobutamine stress echocardiography, CCTA and coronary angiography would be a safe and feasible approach in LT recipients [ 27 ]. However, considering the medical cost and burden, widespread evaluation in low-risk patients is not realistic.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for cardiovascular events after liver transplantation include smoking history (47.3%), obesity (27.6%), diabetes mellitus (26.0%), hypertension (17.8%), family history (17.0%) or prior history of heart disease (6.0%), and hypercholesterolemia (7.2%) [54]. Van Wagner and colleagues also revealed that the following factors are associated with MACE: age, ethnicity, health care status, hospitalization status, socioeconomic status, recipient functional status at transplant, MELD score, cause of ESLD, complications of ESLD at LT such as hepatic encephalopathy, spontaneous bacterial peritonitis, etc.…”
Section: Electrocardiographymentioning
confidence: 99%
“…In this issue of Liver Transplantation , Robertson et al ( 7 ) report the results of the cardiac assessment protocol for LT candidates set in the Victorian Liver Transplant Unit (Australia) in 2010. Having included 569 patients until 2017, it is one of the largest single‐center studies of its kind.…”
mentioning
confidence: 99%
“…However, there is growing evidence showing the limitations of stress tests in patient with cirrhosis, (5) and new noninvasive cardiac imaging techniques, particularly coronary computed tomography angiography (CCTA) with calcium score, are being incorporated in clinical practice. Considering the worsening cardiovascular profile of our patients, the impact of cardiovascular disease on post-LT outcomes, and the limited experience with noninvasive and invasive coronary angiography (CA) in LT candidates, it is imperative for the LT community to be able to explore and compare the efficacy and safety of different protocols approaching the diagnosis of silent CAD before LT. (5) In this issue of Liver Transplantation, Robertson et al (7) report the results of the cardiac assessment protocol for LT candidates set in the Victorian Liver Transplant Unit (Australia) in 2010. Having included 569 patients until 2017, it is one of the largest single-center studies of its kind.…”
mentioning
confidence: 99%